Effect of botulinum toxin infiltration in the lateral muscles of the abdominal wall as an adjuvant for the repair of complex incisional hernias: a case series - Sanchez-Rubio, Luis Fernando (2025)
Introduction: The infiltration of botulinum toxin type A causes chemical denervation of the abdominal wall muscles surrounding the hernia defects of complex eventrations, favoring their repair. Report: 11 cases aren presented with complex eventrations, whose lateral muscle complexes were infiltrated, with botulinum toxin type A (Botox®), as a prehabilitative measure. In the post-infiltration tomographic images, we observed a decrease in the transverse diameter of the right lateral complex between 0.2 to 2 cm and between 0.6 to 1.5 cm on the left side, which represented a reduction of 38% and 40% respectively. In more than 90% of cases, complete fascial closure of the defect was achieved. Conclusion: The use of botulinum toxin type A, in complex incisional hernias, due to its relaxing action on the infiltrated muscles, causes thinning, therefore muscle elongation, favoring aponeurotic closure without tension.